(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Let ???? be a graph with ???? vertices and ???? edges. Let ????: ????(????) → 1,2, … , ???? + ???? be an injective function. For a vertex labeling f, the induced edge labeling ????(???? = ????????) is defined by ????(????) = ⌈√????(????)2+????(????)????(????)+????(????)2 3 ⌉ ???????? ⌊√????(????)2+????(????)????(????)+????(????)2 3 ⌋,then the resulting edge labels are distinct. In this case ???? is called Super Stolarsky-3 Mean labeling of ????. In this paper we investigate Super Stolarsky-3 Mean labeling of line graph.